Miniaturization with Metamaterial of a Triple Band PIFA Antenna for Wi-Fi Communication - Axel Hemsy; Juan Eduardo Ise; Fernando Alberto Miranda Bonomi; Miguel Ángel Cabrera; Mariano Fagre (Revista Elektrón)
In this work, a triple-band planar inverted F antenna (PIFA) was designed and modeled at unlicensed WiFi frequencies (2.4, 5 and 6 GHz). In the proposal made, a metamaterial unit cell was used that was replicated in the ground plane, obtaining a reduction in the size of the antenna with respect to others already published. The cell geometry is based on Minkowski fractal. A J-shaped slot was made in the patch that allowed the resonance frequencies to be adjusted to those of WiFi. A radiation efficiency of around 23% was obtained for the 2.4 GHz band, higher than 74% in the 5 GHz band and 96% in the 6 GHz band.